2013
DOI: 10.1108/00368791311303474
|View full text |Cite
|
Sign up to set email alerts
|

A study of misaligned hole‐entry worn journal bearing operating in turbulent regime

Abstract: Purpose -The purpose of this paper is to study theoretically the combined influence of journal misalignment and wear on the performance of a holeentry hybrid journal bearing system. The bearing is assumed to be operating in a turbulent regime. Design/methodology/approach -The modified Reynolds equation based on Constantinescu lubrication theory has been solved by using finite element method together with orifice and capillary restrictors flow equations as a constrain together with appropriate boundary conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, the governing Reynold’s equation is solved by Galerkin’s method of finite element analysis, and an appropriate iterative solution procedure is used to establish the matched steady-state solution of the lubricant flow region with suitable boundary conditions. The computation of unknown fluid film pressure is obtained by solving global system equation (equation 7) (Ram and Sharma, 2013). In this method, complete fluid film domain is discretized into finite element subdomain as shown in Figure 2(b) and (c).…”
Section: Solution Schemementioning
confidence: 99%
“…In this study, the governing Reynold’s equation is solved by Galerkin’s method of finite element analysis, and an appropriate iterative solution procedure is used to establish the matched steady-state solution of the lubricant flow region with suitable boundary conditions. The computation of unknown fluid film pressure is obtained by solving global system equation (equation 7) (Ram and Sharma, 2013). In this method, complete fluid film domain is discretized into finite element subdomain as shown in Figure 2(b) and (c).…”
Section: Solution Schemementioning
confidence: 99%
“…They found that the friction coefficient generally increases with increasing wear depth as well as misalignment and Sommerfeld number. Ram and Sharma [120] in 2013 studied the combined influence of journal misalignment and wear on the performance of a hole-entry hybrid journal bearing system under turbulence theoretically. They solved modified Reynolds equation based on the Constantinescu lubrication theory by using the finite element method together with orifice and capillary restrictors flow equations as a constraint.…”
Section: Wear Effectsmentioning
confidence: 99%
“…Afterword, Awasthi et al (2007) studied the performance of non-recessed hybrid journal bearing with the effect of wear due to start and stop operations. Thereafter, Ram and Sharma (2013) presented theoretical study concerning combined influence of misalignment and wear on the performance of hole entry hybrid journal bearing.…”
Section: Introductionmentioning
confidence: 99%